2016
DOI: 10.1364/oe.24.001358
|View full text |Cite
|
Sign up to set email alerts
|

Study of GeSn based heterostructures: towards optimized group IV MQW LEDs

Abstract: We present results on CVD growth and electro-optical characterization of Ge(0.92)Sn(0.08)/Ge p-i-n heterostructure diodes. The suitability of Ge as barriers for direct bandgap GeSn active layers in different LED geometries, such as double heterostructures and multi quantum wells is discussed based on electroluminescence data. Theoretical calculations by effective mass and 6 band k∙p method reveal low barrier heights for this specific structure. Best configurations offer only a maximum barrier height for electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The successful demonstration of direct bandgap GeSn light emitting diodes (LEDs), and optically-pumped GeSn lasers, [10][11][12][13][14] indicates the great potential of GeSn for Si-based light sources. GeSn LEDs with double heterostructures (DHS) 11,[15][16][17][18][19][20][21][22] and quantum wells (QWs) [23][24][25][26][27][28][29][30][31] have been reported. It is generally acknowledged that the QW structures could be applied to the LEDs and lasers to improve their device performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] The successful demonstration of direct bandgap GeSn light emitting diodes (LEDs), and optically-pumped GeSn lasers, [10][11][12][13][14] indicates the great potential of GeSn for Si-based light sources. GeSn LEDs with double heterostructures (DHS) 11,[15][16][17][18][19][20][21][22] and quantum wells (QWs) [23][24][25][26][27][28][29][30][31] have been reported. It is generally acknowledged that the QW structures could be applied to the LEDs and lasers to improve their device performance.…”
mentioning
confidence: 99%
“…It is generally acknowledged that the QW structures could be applied to the LEDs and lasers to improve their device performance. LEDs based on the Ge/GeSn/Ge QW structure have been demonstrated, 27 whose detailed analysis suggested that using Ge as a barrier did not provide the desired carrier confinement, and thereupon use of the ternary material SiGeSn as the barrier was proposed, since the bandgap energy and lattice constant of SiGeSn alloys can be tuned independently. The SiGeSn/GeSn/SiGeSn QWs were grown and characterized recently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the band alignment with Ge barriers, the GeSn/SiGeSn configuration offers a clear Type-I band alignment, confining both electrons and holes inside the well. Holes of the GeSn/Ge structure are more confined in the barrier than in the well [6]. In the GeSn/Ge structure the holes actually pile up in the barrier, rather than in the well layers.…”
Section: Gesn-based Light Emitting Diodesmentioning
confidence: 99%
“…While room temperature electroluminescence at low current densities from homojunction light emitting diodes (LEDs), relying on the direct band gap, has already been demonstrated [6][7][8][9] , optically-pumped lasers still suffer from low maximum operating temperatures 3 . Those may be overcome by decreasing the residual compressive strain in the device by more elaborate geometries, like under-etched micro-disk resonators, or by using quantum effects in heterostructures, where charge carriers are confined in a quantum well or a quantum dot 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%